Techno-environmental analysis of battery storage for grid level energy services - Chowdhury, Jahedul Islam; Balta-Ozkan, Nazmiye; Goglio, Pietro; Hu, Yukun; Varga, Liz; McCabe, Leah (Elsevier, 2020)
With more and more renewable energy sources (RES) going into power grids, the balancing of supply and demand during peak times will be a growing challenge due to the inherent intermittency and unpredictable nature of RES. Grid level batteries can store energy when there is excess generation from wind and solar and discharge it to meet variable peak demand that is currently supplied by combined cycle gas turbine (CCGT) plants in the UK. This paper assesses the potential of battery storage to replace CCGT in responding to variable peak demand for current and future energy scenarios (FES) in the UK from technical and environmental perspectives. Results from technical analysis show that batteries, assuming size is optimised for different supply and demand scenarios proposed by the National Grid, are able to supply 6.04%, 13.5% and 29.1% of the total variable peak demand in 2016, 2020 and 2035, respectively while CCGT plants supply the rest of the demand. Particularly, to phase out CCGT variable generation from the UK grid in 2035, electricity supply from wind and solar needs to increase by 1.33 times their predicted supply in National Grid’s FES. The environmental implications of replacing CCGT by batteries are studied and compared through a simplified life cycle assessment (LCA). Results from LCA studies show that if batteries are used in place of CCGT, it can reduce up to 87% of greenhouse gas emissions and that is an estimated 1.98 MtCO2 eq. for an optimal supply, 29.1%, of variable peak demand in 2035
Keywords: life cycle assessment (LCA); combined cycle gas turbine (CCGT); renewable integration; energy system modelling; Battery energy storage system (BESS)